Analisis Keputusan Rusia dalam Operasi Militer Khusus ke Ukraina 2022 melalui Pendekatan Decision-Making Theory - Wahyuningtias , Putri Diah; Wibowo, Prihandono (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze Russia's decision to launch Special Military Operations against Ukraine in 2022 using a Decision-Making Theory approach. The primary background of this research is the geopolitical tension related to Ukraine's potential NATO membership, which was perceived as a direct threat to Russia's national security. The method employed in this study is a qualitative analysis based on a literature review, including official documents, academic articles, and other secondary data sources. The findings reveal that Russia's decision was influenced by a security dilemma stemming from NATO's expansion in Eastern Europe and Ukraine's increasing dependence on the West. From an economic perspective, Ukraine's reliance on Russian energy resources became one of the strategic factors in this decision. The study shows that Russia's decision was driven not only by external factors, such as NATO, but also by internal factors, including domestic political support and strong military capabilities. In conclusion, Russia’s decision to launch military operations was a preventive measure to maintain its influence in Eastern Europe, safeguard its national interests, and prevent Ukraine from joining NATO, which is perceived as a long-term threat to Russia's security.